ANALISIS PERSEDIAAN BAHAN BAKU ROTI DENGAN METODE ECONOMIC ORDER QUANTYTY(EOQ) DAN JUST IN TIME(JIT) PADA PERUSAHAAN ROTI - Nuzul Eky Fachrezy; Widya Setiafindari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to evaluate raw material inventory control at the UMKM Asy-syifa Bakery and determine the most economical order quantities and costs. The data used is a report on the purchase and use of wheat flour raw materials at the UMKM Asy-syifa Bakery in 2023. The data analysis technique compares raw material inventory costs between the Economic Order Quantity Method and the Just In Time Method. The standard requirement for wheat flour is 6050 kilograms, sugar is 651 kilograms, eggs are 480 kilograms, margarine is 120 cartons, and milk is 360 liters. Based on the calculations that have been carried out, the cost of raw material inventory using the Order Quantity Economic method is 2,746,327 rupiah and the cost using the Just In Time method is 3,446 231 rupiah, with a difference in 2023 of 699,904 rupiah, which is equivalent to around 20.3% of the total cost inventory. The results show that the EOQ method is more efficient than Just In Time.